2019
DOI: 10.1093/mnras/stz1487
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical evolution of star-forming regions: III. Unbound stars and predictions for Gaia

Abstract: We use N-body simulations to probe the early phases of the dynamical evolution of star-forming regions and focus on mass and velocity distributions of unbound stars. In this parameter space study, we vary the initial virial ratio and degree of spatial and kinematic substructure and analyse the fraction of stars that become unbound in two different mass classes (above and below 8 M ⊙ ). We find that the fraction of unbound stars differs depending on the initial conditions. After 10 Myr, in initially highly subv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 84 publications
5
27
0
Order By: Relevance
“…While simulations show (Schoettler et al 2019) that we can expect to find RW stars where only one of their velocity components would identify them as a RW or WW star, there can be other explanations such as the possible binarity of the system. In this case, the difference in RV measurements from two surveys hint at this star being part of a binary, located in the ONC centre.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…While simulations show (Schoettler et al 2019) that we can expect to find RW stars where only one of their velocity components would identify them as a RW or WW star, there can be other explanations such as the possible binarity of the system. In this case, the difference in RV measurements from two surveys hint at this star being part of a binary, located in the ONC centre.…”
Section: Discussionmentioning
confidence: 88%
“…This large number of cluster stars and higher local stellar density can increase the likelihood of dynamical ejections (e.g. Oh & Kroupa 2016;Farias et al 2019;Schoettler et al 2019). Hillenbrand (1997) considered the projected size of the ONC in two dimensions to be 2.5 × 4.5 pc and Kroupa et al (2018) suggested the cluster to have a nominal radius of ∼2.5 pc.…”
Section: Search Targetmentioning
confidence: 99%
See 3 more Smart Citations